New classes of exact solutions for a problem of many bodies that attract one another according to an arbitrary law depending on the distances between bodies - Gadomskii, L. Ya.; Grebenikov, E. A.; Gurskaya, A. R.; Zemtsova, N. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
The existence of a 5-parameter family of exact solutions is proved for differential equations describing the motion of many bodies that attract one another according to an arbitrary law depending on the distances between the bodies.